Evaluation of irradiation and Termin-8® addition to spray-dried animal plasma, base mix and/or whole diet on growth performance of nursery pigs - Musser, R.E.; Cannon, W.N.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies were conducted to evaluate the effects of irradiation of spray-dried animal plasma and Termin-8 treatment to spray-dried animal plasma, base mix (specialty protein products, milk products, ground oat groats, soy flour, flow agent, vitamins, and minerals), or whole diet on nursery pig performance. Overall (d 0 to 14) in Exp. 1, pigs fed diets containing irradiated plasma had increased ADG and pigs fed Termin-8® treated plasma had increased ADG and ADFI compared to pigs fed diets with regular plasma or whole diets (containing either regular or irradiated plasma) treated with Termin-8. No differences in F/G were observed among treatments. In Exp. 2, pigs fed diets that contained either animal plasma or base mix treated with Termin-8 in the SEW diet had increased ADG and F/G from d 0 to 13 compared to no Termin-8 treatment, but no differences were observed overall (d 0 to 40). Therefore, the use of irradiated spray-dried animal plasma and Termin-8 treated spray-dried animal plasma and base mix improves growth performance in nursery pigs during the initial period after weaning.
Keywords: Swine; Irradiation; Termin-8®; Nursery pig